(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2019)
Considering the toxic action of P. aquilinum bracken for vertebrates, its insecticidal activity and potential use in agricultural pest control was verified, testing its effects on S. frugiperda. Crude ethanolic extract was made with the aerial part of P. aquilinum, being incorporated into artificial diet (control or extract-free, 1% and 2%) with 50 replicates (caterpillars). There was significant mortality (34% and 86%) at concentrations of 1% and 2%, respectively, compared to control (10%). In treatments at 1% (20.03 days) and 2% (20.42 days), larval stage prolongation (13.51 days) was observed in the control treatment. On the 3rd, 6th, 9th and 12th days after treatment, there was weight reduction, and the 2% treatment resulted in larvae 73% lighter than the control did at day 12. The pupae of the 2% treatment were lighter than the others. In conclusion, 1% and 2% of P. aquilinum ethanolic extract extended the larval cycle, decreased the larvae’s and pupae’s weight, and, at a concentration of 2%, caused effective mortality of S. frugiperda.